2014
DOI: 10.1038/srep07187
|View full text |Cite
|
Sign up to set email alerts
|

Protein-protein Interaction Networks of E. coli and S. cerevisiae are similar

Abstract: Only recently novel high-throughput binary interaction data in E. coli became available that allowed us to compare experimentally obtained protein-protein interaction networks of prokaryotes and eukaryotes (i.e. E. coli and S. cerevisiae). Utilizing binary-Y2H, co-complex and binary literature curated interaction sets in both organisms we found that characteristics of interaction sets that were determined with the same experimental methods were strikingly similar. While essentiality is frequently considered a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…We determined that Y. pestis follows the centrality-lethality rule in vitro ( r 2 =0.85, P =0.0030, Fig. 1a), as observed in other prokaryotes7, but not in vivo ( r 2 =0.38, P =0.19, Fig. 1a).…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…We determined that Y. pestis follows the centrality-lethality rule in vitro ( r 2 =0.85, P =0.0030, Fig. 1a), as observed in other prokaryotes7, but not in vivo ( r 2 =0.38, P =0.19, Fig. 1a).…”
Section: Resultsmentioning
confidence: 62%
“…This rule holds for many organisms, both prokaryotes and eukaryotes578. However, the extension of this rule to infectious organisms such as bacteria is not straightforward.…”
mentioning
confidence: 99%
“…Furthermore, we found that interactions that involve critical proteins are enriched with essential genes. Such a results is a corollary to previous results, indicating that essential proteins tend to cluster together in protein interaction networks of different organisms . Furthermore, critical proteins have already been observed to be essential .…”
Section: Discussionmentioning
confidence: 99%
“…The reason is that the transient interactions may not remain conserved in the evolution and genes involved in these kinds of interactions may not exhibit high co-expression. On the other hand, more stable interactions and protein complexes are highly conserved in the evolution [34, 35] and the interacting proteins are highly co-expressed [35]. …”
Section: Discussionmentioning
confidence: 99%